Revealing 60 years of Earthquake Swarms in the Southern Red Sea, Afar and the Gulf of Aden - Ruch, Joël; Keir, Derek; Passarelli, Luigi; Di Giacomo, Domenico; Ogubazghi, Ghebrebrhan; Jónsson, Sigurjón (Frontiers in Earth Science, 2021)
Earthquake swarms occur sporadically at divergent plate boundaries but their recurrence over multiple decades and relation to magmatic spreading activity remain poorly understood. Here we study more than 100 earthquake swarms over a 60-year period in the southern Red Sea, Afar, and Gulf of Aden region. We first compiled an earthquake-swarm catalogue by integrating reexamined global and local earthquake catalogues from 1960 to 2020. This yielded 134 earthquake swarms that mainly cluster in 19 different areas in the study region, showing that in most cases swarms recur every few decades in the same area. The swarms exhibit a range of earthquake magnitudes and often include multiple M3 to M5 events with some swarms having occasional larger earthquakes of up to over M6, primarily in southern Afar. Many of the earthquake swarms were clearly associated with rifting events, consisting of magmatic intrusions, surface faulting, and in some cases volcanic eruptions. Together, the swarms suggest that extension at these divergent plate boundaries occurs episodically along <100 km long segments, some of which were previously unrecognized. Within the study region, the Gulf of Aden shows the strongest swarm activity, followed by Afar and then the southern Red Sea. The results show that the three areas were subject to an almost synchronous increase of earthquake-swarm activity from 2003 to 2013 in the form of three rifting episodes and at least seven volcanic eruptions, indicating an overall increase of magma supply or a regional rifting cycle affecting the entire study region.